Pengaruh Artificial Intelligence Terhadap Sistem Informasi Akuntansi: Studi Kasus Virtual Account Bank Syariah Indonesia - Tanjung, Siti Khodijah; Adinda; Sabila, Dinda Thalia; Zufrizal (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study investigates how Artificial Intelligence impacts accounting information systems. This case study analyzes the use of virtual accounts at Bank Indonesia Syariah. that accounting processes such as automatic reconciliation, transaction identification, and financial reporting The application of artificial intelligence can optimize in the virtual account system, including machine learning and natural learning. This study uses qualitative case studies to collect data from an additional 66 respondents. This study explains how the Islamic banking sector develops an Artificial Intelligence-based accounting information system